Loss of ZNF215 imprinting is associated with poor five-year survival in patients with cytogenetically abnormal-acute myeloid leukemia - Yang, Ming-Yu; Lin, Pai-Mei; Yang, Chao-Hui; Hu, Ming-Luen; Chen, I-Ya; Lin, Sheng-Fung; Hsu, Cheng-Ming (Blood cells, molecules, & diseases, 2021)
Genomic imprinting is a form of epigenetic regulation and imprinted genes are silenced in a parental-specific manner. Imprinting is associated with various human diseases and cancers, but its roles in leukemogenesis remains elusive. In this study, the expression of a panel of 16 human imprinted genes was investigated using real-time quantitative polymerase chain reaction and 8 of them were further validated in 114 patients newly diagnosed with cytogenetically abnormal-acute myeloid leukemia (CA-AML) and 85 healthy subjects. Our results demonstrated upregulated expression of 8 imprinted genes (C15orf2, COPG2, H19, IGF2, PEG3-AS1, PRIM2, SLC22A3 and ZNF215) was observed in patients with CA-AML (p < 0.001). Patients' survival days were negatively correlated with the expression levels of H19 (p = 0.024), PGE3-AS1 (p = 0.038), and ZNF215 (p = 0.012). Multivariate logistic regression analysis further revealed the expression level ZNF215 can be used as a predictor for five-year survival for patients with CA-AML (p = 0.009) with a hazard ratio of 0.870 (95.0% confident interval: 0.784–0.965). Our results demonstrated that loss of imprinting of imprinted genes is critical for the leukemogenesis of AML under CA condition, and loss of ZNF215 imprinting is associated with poor five-year survival of patients with CA-AML.